Upconversion Yb3+/Er3+:Gadolinium Gallium Garnet Nanocrystals for White-Light Emission and Optical Thermometry - ERDEM, MURAT (AMER CHEMICAL SOC, 2021)
The fabrication of size-dependent rare earth ion-doped materials for photonic devices has attracted interest in the search for color tunability and noncontact temperature sensing properties with high sensitivity. Sol-gel Pechini is an appropriate method compared to other methods to prepare Yb3+/Er3+:gadolinium gallium garnet (GGG) crystals at the nanoscale. This work presents a study of white-light emission and optical thermometry properties of Yb3+/Er3+:GGG nanocrystals based on the upconversion (UC) blue, green, and red emissions observed under 975 nm laser excitation. The color coordinates of the studied nanocrystals were affected by the crystalline size. Yb3+ (2 mol %)/Er3+(1 mol %):GGG nanocrystals have the highest maximum absolute sensitivities of 0.0028 K-1 at 378 K and 0.0041 K-1 at 561 K for 17 and 45 nm crystalline sizes, respectively. In light of the observations, Yb3+/Er3+:GGG may be a good candidate material for use in white light and optical temperature sensing.
Keywords: nanophosphors; gadolinium gallium garnet; upconversion; color parameters; optical thermometry; LUMINESCENCE PROPERTIES; SINGLE-CRYSTAL; THIN-FILMS; ER3+; LN; FLUORESCENCE; PERFORMANCE; LANTHANIDE; DEPENDENCE; PHOSPHOR